Comparison on Impact Toughness of High-Strength Metastable β Titanium Alloy with Bimodal and Lamellar Microstructures - Jing Wang; Yongqing Zhao; Qinyang Zhao; Chao Lei; Wei Zhou; Weidong Zeng (Metals, 2022)
The impact toughness of a high-strength metastable β titanium alloy (Ti-5Cr-4Al-4Zr-3Mo-2W-0.8Fe) with two typical microstructures is studied by Charpy impact tests. The bimodal microstructure (BM) and the lamellar microstructure (LM) are obtained by the solution and aging treatments and the β annealing, slow cooling and aging treatments, respectively. In the impact crack initiation process, the deformation capacities of the primary α (αp) phase, secondary α (αs) phase and transformed β (βt) matrix in the BM are very different, and the stress gradient at the interface of the three causes the crack initiation. The lamellar α (αl) phase and βt in the LM satisfy the BOR relationship, and the effective slip transfer between α and β phases slows down the crack initiation. Meanwhile, the appearance of deformation twins in the LM improves the crack initiation energy. In the crack propagation process, the lack of coordinated deformation between the α and β phases in the BM leads to rapid crack propagation. In the LM, the deformation of αl and βt is relatively more coordinated, so the severe plastic deformation is only concentrated near the crack and at the interface. The secondary crack initiation and the crack propagation along the twin boundary reduce the stress concentration at the crack tip. The deformation twins and zigzag propagation path can improve the crack propagation energy. To summarize, the alloy with LM exhibits better impact toughness than the alloy with BM.